Antibacterial Extract of Red Dragon Fruit (Hylocereus polyrhizus) Peel Extract against ESBL-Producing Klebsiella pneumoniae - Rivaldy, Naufal; Kartika, Andy Visi; Karim, Marzelina; Sodiqah, Yani; Anggita, Dwi (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The rising prevalence of infections caused by Extended-Spectrum Beta-Lactamase (ESBL)-producing Klebsiella pneumoniae necessitates the search for alternative antibacterial agents. Red dragon fruit (Hylocereus polyrhizus) peel is a potential source of bioactive compounds. This study aimed to evaluate the in vitro antibacterial activity of red dragon fruit peel extract against ESBL-producing K. pneumoniae. The bacteria were isolated and identified via culture on MacConkey agar, Gram staining, and biochemical tests. The peel was extracted using 96% ethanol via maceration. Antibacterial activity was assessed using the disk diffusion method on Mueller-Hinton agar with extract concentrations of 20%, 40%, 60%, 80%, and 100% (v/v), with three replicates per concentration. Meropenem (10 µg) and DMSO served as positive and negative controls. The extract exhibited concentration-dependent antibacterial activity, with mean inhibition zone diameters increasing from 5,6 ± 0,3 mm at 20% to 6,1 ± 0,2 mm at 100%. The positive control produced a 30,2 ± 0,5 mm zone, while the negative control showed no inhibition. One-way ANOVA confirmed significant differences between groups (p-value < 0,05). Red dragon fruit peel extract demonstrated promising in vitro antibacterial activity against ESBL-producing K. pneumoniae, although its potency was considerably lower than meropenem.